Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XIV. Chemical Pulps and Writing and Printing Papers from Sterculia Campanulata, Wall. - Bhat, R. V.; Virmani, K. C. (Indian Forester, 1953)
Laboratory experiments on the Sulphate digestion of the wood of Sterculia campanulata, Wall. (papita) are described. The bleached chemical pulps were characterized by high strength properties. The average fibre length of the chemical pulp was 1.49 mm. The results of the pilot plant experiments on the production of chemical pulps and writing and printing papers are included. This investigation has indicated that this wood is a suitable raw material for the production of writing and printing papers. A sample of writing paper made entirely from S. campanulata pulp and another of printing paper made from a mixture of 68% S. campanulata pulp and 32% bamboo pulp are appended.